THE DYNAMICS OF SOCIAL STIGMA TOWARD PATIENTS WITH TUBERCULOSIS AND THEIR FAMILIES IN MEDAN CITY - Risky Hasibuan; Muhammad Jailani (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Tuberculosis (TB) remains a major public health issue that affects not only physical health but also generates social challenges in the form of stigma toward patients and their families. This study aims to analyze the dynamics of social stigma experienced by tuberculosis patients and their family members in Medan City, Indonesia. A qualitative approach with a phenomenological design was employed to explore the lived experiences and meanings attributed by the participants. Data were collected through in depth interviews with TB patients, their family members, and healthcare workers involved in TB management. The findings reveal that stigma against TB patients remains prevalent within the community. The identified forms of stigma include social exclusion, discriminatory treatment, negative labeling, and fear of disease transmission. In addition, family members experience secondary stigma, reflected in changes in community attitudes and feelings of shame when a relative's TB status becomes publicly known. Such stigma adversely affects patients' psychological wellbeing, leading to reduced self confidence, social withdrawal, and reluctance to disclose their illness. Conversely, family support plays a significant role in strengthening patients' motivation to adhere to treatment and cope with social pressures. The study further demonstrates that stigma is shaped by social interactions and inadequate public knowledge of tuberculosis. Therefore, continuous health education, strengthened social support, and the implementation of more inclusive approaches to TB care are essential to reducing stigma and improving the well being of individuals affected by tuberculosis